Virtual prototype and experimental research on spatial kinematics of telescopic robotic excavator. (15th May 2017) - Hongxin, Cui; Ke, Feng; Huanliang, Li; Jinhua, Han
In order to achieve autonomous operation, the kinematics model and experiment system of telescopic excavator are studied. Firstly, the operation space of the robotic excavator is classified and mapping models between different spaces are established based on the D-H method and geometrical relationship method. Then, the virtual prototype of the telescopic robotic excavator is built based on the SimMechanics software, leveling operation and digging operation are simulated; kinematics model and virtual prototype are tested and verified. Finally, experimental system is developed and trajectory tracking experiment is carried out. By comparing with the simulation results, the validity of the proposed control scheme is verified. The research of this article laid foundations for further study and application.